Chemical Speciation of Organic and Inorganic components of Environmental and Biological Interest in Natural Fluids: Behaviour, Interaction and Sequestration - Crea, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The International Union of Pure and Applied Chemistry (IUPAC) defines the term "speciation" as the distribution of an element amongst defined chemical species in a system, while the process leading to quantitative estimation of the content of different species is called speciation analysis. The chemical speciation of elements in natural waters and biological fluids is a key topic, essential for discussing the chemical reactivity of constituents in these systems. It is well understood that it is the chemical form of a metal or metalloids that determines its reactivity, lifetime, and fate in the environment. Chemical speciation now involves various sectors of the sciences, from chemistry to biology, biochemistry, and environmental sciences, since-as is well known-the total concentration, alone, of an inorganic or organic component (metal or ligand) in a multicomponent natural system (fresh water, sea water, biological fluids, soil, etc.) is insufficient for a comprehensive understand of its behavior in those contests.